GENETICS OF PSORIASIS AND PSORIATIC ARTHRITIS - V. Ibba; M. Piga; G. Porru; G. Passiu; A. Mameli; A. Vacca; A. Cauli; A. Mathieu; V. Mura; S. Anna (PAGEPress Publications, 2011)
Psoriasis and psoriatic arthritis are linked diseases characterised by (distinct ?) immune-mediated pathogenetic mechanisms and by a genetic background interacting with environmental factors. Some candidate susceptibility genes have been studied extensively; they include HLA genes, genes within the HLA region and genes outside the HLA region; among them corneodesmosin and other genes of PSORS1 region, MICA and TNF-a polymorphisms. The main findings in the literature are discussed. Key words: Genetics, psosriasis, psoriatic arthritis